Diagnosis and Control of Parasitic Diseases - Ram, Hira; Garg, Rajat; Samanta, S.; Prasad, Arvind; Banerjee, P. S. (Indian Farming, 2015)
Parasitologists at IVRI are making efforts to control important parasitic diseases of domestic animals with the aim of ‘one health’ concept to increase productivity and food security. Presently, the major thrust areas of research include development of sensitive diagnostics and effective vaccines, epidemiology of animal parasites including those of zoonotic importance, genetic characterization of economically important parasites, detection of anthelmintic and acaricide resistance and development of herbal acaricides.